التغيرات الموسمية لبعض العناصر المغذية في مياه نهر دجلة ضمن محافظة ميسان - عبود عبد الغفور, سمير; هيثم جبار, مصطفى; كريم حسان, ثائر; جاسم محمد, علاء (University of Thi-Qar Journal of Science, 2011)
This research was contained study of nitrate and phosphate concentration as well aspH , EC , turbidity , and DO for water of Tigris River within Misan Governorate. Sampleswere collected from six stations (Ali Al-Garbi , Amara Al-Moahad, AL-Jumhoriah bridge ,Al-Wihda, Qalat Saleh, and Al-Azir) during two seasons , Summer 2008 and Winter 2009 .Mean of nitrate concentration in both seasons were (5.616 and 5.008) mg.1-1 respectively.The high concentration was recorded in Al-Azir station in both seasons (6.08 and 5.29)mg.1-1 respectively, and high significant correlation was found between nitrateconcentration and turbidity (0.744**, 0.772**) seasonally. Mean of phosphate concentrationin Tiger River were (0.905, 0.963) mg.1-1 during different seasons , high significantcorrelation was found between phosphate concentration and turbidity (0.793**, 0.814**)respectively. Generally, concentration of nitrate and phosphate increased forward south